Women, Erotica and Citizenship in the Eighteenth Century: Virginia and Megara as Iberian Tragic Heroines. Issue 2 (3rd May 2016) - Pinto, Isabel
Abstract: This article addresses eighteenth-century tragedy from the point of view of its heroines. The author considers the neoclassical reworking of tragic events, with its empowering of ancient, and also modern, women, which proliferated in the Iberian Peninsula. Within this framework, Virginia and Megara, two tragedies by male authors, provide powerful depictions of female civic engagement, drawing both on a radical stance of deciding upon life and death, and on the portrayal of an untamed body that is emancipated from private male desire to embrace nationhood. In terms of the history of sexuality, these tragic heroines help to unravel the complex interrelationships between death, eroticism and citizenship.